2018
DOI: 10.1002/hipo.22965
|View full text |Cite
|
Sign up to set email alerts
|

Delayed injury of hippocampal interneurons after neonatal hypoxia‐ischemia and therapeutic hypothermia in a murine model

Abstract: Delayed hippocampal injury and memory impairments follow neonatal hypoxia-ischemia (HI) despite the use of therapeutic hypothermia (TH). Death of hippocampal pyramidal cells occurs acutely after HI, but characterization of delayed cell death and injury of interneurons (INs) is unknown. We hypothesize that injury of INs after HI is: (i) asynchronous to that of pyramidal cells, (ii) independent of injury severity, and (iii) unresponsive to TH. HI was induced in C57BL6 mice at p10 with unilateral right carotid li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 70 publications
5
46
2
Order By: Relevance
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 92%
“…Of note, we previously reported that connexin43 hemichannel blockade could also reduce loss of striatal interneurons following HI in term fetal sheep [22]. Further, a reduction in interneuron loss in the cortex with erythropoietin treatment, [142] hippocampus with therapeutic hypothermia, [42] and striatum with bone marrow-derived mesenchymal stem cells [36] was reported following HI in neonatal rats and in the striatum with nitric oxide inhibition [33] or therapeutic hypothermia [143] following HI in preterm fetal sheep. Future studies are required to determine the exact timing of interneuron loss, altered PNN development, and expression of ECM remodeling enzymes after HI to help optimize treatment strategies.…”
Section: Discussionmentioning
confidence: 88%
“…Also, GAP-43 expressing neurons may be more resistant to the direct ischemic event. It has been suggested that different types of neurons are differently susceptible to early and delayed cell death after ischemic injuries [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sections obtained from animals killed 24 h or 7 days after normal saline or poly I:C exposure were used to assess astroglia (GFAP) and microglia (Iba1) activation and overall microscopic evidence of injury (Nissl counterstaining for GFAP IHC). Floating IHC was performed as previously described (Chavez-Valdez et al, 2018) with whole rabbit antisera anti-GFAP (DAKO/Agilent Technologies, Santa Clara, CA, United States; 1:1000), or anti-Iba1 (Wako Chemicals USA, Inc., Richmond, VA, United States; 1:500) followed by goat anti-rabbit antibody (1:200) used as the secondary antibody using DAB as the chromogen for GFAP and using Alexa Fluor 568 for immunofluorescence for Iba1. Cresyl-violet (CV) counterstaining was performed in those sections previously immunostained for GFAP to assess histological structure.…”
Section: Methodsmentioning
confidence: 99%